The Doctrine of Predestination According To The Old Testament - Yuangga Kurnia Yahya; Mohammad Rafdi Ilahi (Journal of Comparative Study of Religions (JCSR), 2021)
This study aims to find the meaning of the doctrine of predestination in theold testament and seek the basis of the conflict between Christian theologians.In this study, researchers used a normative theological approach to explain thedoctrine of predestination from a Christian point of view. While in understandingthe predestination verses, researchers use a hermeneutic approach. From thisstudy, researchers concluded that the doctrine of predestination is a doctrinethat discusses whether or not human beings save in the world and enterhuman heaven or hell later. The difference in understanding this doctrine isdue to the contradiction of the verses in the old testament and the differences inunderstanding the doctrines relating to this doctrine of predestination, such asthe doctrine of sin, the salvation and the fall of Adam from heaven.